Factors Associated With Hypertension Control Behavior In The Elderly At The Merdeka Community Health Center, Palembang In 2025 - Fantia Tria Siska; Nur Asbon; Irdan Irdan (International Journal of Health Engineering and Technology, 2026)
Hypertension is a major non-communicable disease with a high prevalence in the elderly at the Merdeka Community Health Center in Palembang, influenced by knowledge, diet, and family support. This study aims to analyze the relationship between these factors and hypertension control behavior. Using a quantitative cross-sectional analytical design, the population of hypertensive elderly was 2,167 people with a sample of 106 respondents via simple random sampling. The questionnaire instrument was analyzed univariately (frequency) and bivariately (Chi-Square, α = 0.05) using SPSS. The results showed a significant relationship: knowledge (p = 0.000; OR = 17.667), diet (p = 0.000; OR = 4.453), and family support (p = 0.000; OR = 10.200). The conclusion recommends family education interventions to improve compliance.